Dynamics in Logistics Proceedings of the 6th International Conference LDIC 2018, Bremen, Germany - Freitag, Michael; Kotzab, Herbert; Pannek, Jürgen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
These proceedings contain research presented at the 6th International Conference on Dynamics in Logistics, held in February 2018.The integration of dynamics within the modeling, planning and control of logistic processes and networks has shown to contribute massively to the improvement of the latter. Moreover, diversification of markets and demand has increased both the complexity and the dynamic changes of problems within the area of logistics. To cope with these challenges, it must become possible to identify, describe and analyze such process changes. Moreover, logistic processes and networks must be revised to be rapidly and flexibly adaptable to continuously changing conditions. This book presents new ideas to solve such problems, offering technological, algorithmic and conceptual improvements. It primarily addresses researchers and practitioners in the field of industrial engineering and logistics.
Keywords: Industrial Management; Business logistics; Artificial intelligence; Industrial Management; Logistics; Artificial Intelligence